Pengaruh Motivasi dan Budaya Organisasi Terhadap Kinerja Karyawan PT. Bank Mestika Cabang Tuanku Tambusai Pekanbaru - Rizky, Ahmad; ', Marnis; ', Marzolina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The study was conducted at a branch of Bank Mestika lord Tambusai Pekanbaru and aims to determine the effect of motivation and organizational culture on employee performance Mestika Bank branch lord Tambusai Pekanbaru. The study population was all employees totaling 45 people. Sampling transactions are carried out with models census. The variables used in this study is motivation and organizational culture as an independent variable, and performance as the dependent variable. Data analysis method used is descriptive analysis and multiple linear regression analysis with the help of SPSS tools 17 for windows. The research concludes that the motivation and organizational culture have a significant effect on the performance simultaneously. Partially, the motivation has no significant effect on performance. While organizational culture positive and significant effect on employee performance. Cultural organizations provide a stronger influence on performance than the influence of motuivasi.Keywords: Motivation, Organizational Culture, and Performance